2018
DOI: 10.1002/stem.2888
|View full text |Cite
|
Sign up to set email alerts
|

JAK2V617F Megakaryocytes Promote Hematopoietic Stem/Progenitor Cell Expansion in Mice Through Thrombopoietin/MPL Signaling

Abstract: The myeloproliferative neoplasms (MPNs) are stem cell disorders characterized by hematopoietic stem/progenitor cell (HSPC) expansion and overproduction of mature blood cells. The acquired kinase mutation JAK2V617F plays a central role in these disorders. The mechanisms responsible for HSPC expansion in MPNs are not fully understood, limiting the effectiveness of current treatments. One hallmark feature of the marrow in patients with MPNs is megakaryocyte (MK) hyperplasia. Previously, we reported that JAK2V617F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 57 publications
(112 reference statements)
8
32
0
Order By: Relevance
“…A trend toward a lower level of megakaryocytes in the bone marrow of mice treated with the combination compared with ruxolitinib was also detected (supplemental Figure 6B-C), which could be significant, given the role of megakaryocytes in driving MPN. [70][71][72] Consistent with our observations that INCB053914 antagonized disease that persisted during ruxolitinib treatment in our in vivo model studies ( Figure 6; supplemental Figures 5A and 6A), INCB053914 also effectively antagonized the growth of ruxolitinib persistent SET2 and BaF3-JAK2 VF cells (supplemental Figure 7), supporting the notion that INCB053914 may antagonize ruxolitinib resistance in patients. The ability of PIM inhibition to antagonize a ruxolitinib persistent state further supports a role for PIM in targeted therapy resistance as described in other cancer models.…”
Section: Incb053914 and Ruxolitinib Suppress Jak2 V617f -Driven Tumorsupporting
confidence: 87%
“…A trend toward a lower level of megakaryocytes in the bone marrow of mice treated with the combination compared with ruxolitinib was also detected (supplemental Figure 6B-C), which could be significant, given the role of megakaryocytes in driving MPN. [70][71][72] Consistent with our observations that INCB053914 antagonized disease that persisted during ruxolitinib treatment in our in vivo model studies ( Figure 6; supplemental Figures 5A and 6A), INCB053914 also effectively antagonized the growth of ruxolitinib persistent SET2 and BaF3-JAK2 VF cells (supplemental Figure 7), supporting the notion that INCB053914 may antagonize ruxolitinib resistance in patients. The ability of PIM inhibition to antagonize a ruxolitinib persistent state further supports a role for PIM in targeted therapy resistance as described in other cancer models.…”
Section: Incb053914 and Ruxolitinib Suppress Jak2 V617f -Driven Tumorsupporting
confidence: 87%
“…Yoshihara and colleagues also found that c‐Mpl was critical for the interaction of stem cells with the marrow niche . Thus, neither MK nor E‐SLAM expansion was observed in either strain of mice, despite the presence of the JAK2 V617F ‐positive MKs in both . Taken together, these studies demonstrated that THPO/c‐Mpl signaling is important for MPN HSC expansion in both Tie2 + /FF1 + and PF4 + /FF1 + mice, where HSCs and/or major components of the hematopoietic perivascular niche (ECs and MKs in Tie2 + /FF1 + , and MKs in PF4 + /FF1 + , respectively) bear the JAK2 V617F mutation.…”
Section: Thrombopoietin and Its Receptor C‐mpl Are Important For The mentioning
confidence: 94%
“…Using Jak2 V617F -Pf4iCre mice, Zahn et al showed that Jak2 V617F -mutant megakaryocytes promote the expansion of hematopoietic stem and progenitor cells (HSPCs) in mice ( 41 ). A recent study verified that the expansion of HSPCs was due to constitutively active thrombopoietin/MPL signaling, resulting in increased megakaryocytes, and causing HSPC expansion through cell non-autonomous mechanisms ( 42 ). Moreover, expression of mutant Jak2 in megakaryocytes was sufficient to induce fibrosis and erythropoiesis, the latter due to increased levels of IL6 ( 42 ).…”
Section: Cellular Contributors To Inflammationmentioning
confidence: 96%
“…A recent study verified that the expansion of HSPCs was due to constitutively active thrombopoietin/MPL signaling, resulting in increased megakaryocytes, and causing HSPC expansion through cell non-autonomous mechanisms ( 42 ). Moreover, expression of mutant Jak2 in megakaryocytes was sufficient to induce fibrosis and erythropoiesis, the latter due to increased levels of IL6 ( 42 ). This finding supports other studies showing a cell non-autonomous effect of the Jak2 -mutant clone on wildtype cells ( 40 ).…”
Section: Cellular Contributors To Inflammationmentioning
confidence: 96%
See 1 more Smart Citation